Phytochemical Screening and Antimicrobial Studies of Crateva adansonii Leaf Extract - C.O., Ajanaku; J.O., Echeme; R.C., Mordi; O.O., Ajani; J.A.O., Olugbuyiro; T.F., Owoeye; O.S., Taiwo; J.U., Ataboh (Covenant Journal of Physical and Life Sciences, 2017)
Diverse challenges of microbial infections and upsurge of multi-drug resistant microbes informed the investigation into the phytochemical and antibacterial properties of Crateva adansonii. Cold extraction was carried out using methanol solvent. The crude extract of Crateva adansonii was fractionated into the n-hexane, methanol and chloroform layers successively. The phytochemical screening indicated the presence of alkaloids, saponins, terpenoids, flavonoids and cardiac glycosides. The antimicrobial assay showed that, for Bacillus spp, the organism was sensitive to the chloroform fraction of leaf extract at 1.562 mg/ml. For Microccocus varians, result showed organism was sensitive to the crude extract at 3.125 mg/ml. According to the result of antifungal screening, the n-hexane fraction and crude extract showed activity against Aspergillus niger at 12.500 mg/ml and 3.125 mg/ml respectively. From these results, the crude extract of the leaf of Crateva adansonii shows activity against both bacteria and Fungi; hence, it may might be a good source of new drug for treating infections caused by these pathogens.